2022
DOI: 10.1002/eat.23834
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for new‐onset binge eating, low weight, and self‐harm symptoms in >35,000 individuals in the UK during the COVID‐19 pandemic

Abstract: Objective: The disruption caused by the COVID-19 pandemic has been associated with poor mental health, including increases in eating disorders and self-harm symptoms. We investigated risk and protective factors for the new onset of these symptoms during the pandemic. Method: Data were from the COVID-19 Psychiatry and Neurological Genetics study and the Repeated Assessment of Mental health in Pandemics Study (n = 36,715).Exposures were socio-demographic characteristics, lifetime psychiatric disorder, and COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…These differences may reflect associations between disordered eating, reduced physical activity and poor mental health exacerbated by the pandemic. 20,21 Our finding highlights the need for health services to ensure parity of esteem 22 between physical and mental health conditions when prioritising groups to be supported by weight loss interventions.…”
Section: Discussionmentioning
confidence: 80%
“…These differences may reflect associations between disordered eating, reduced physical activity and poor mental health exacerbated by the pandemic. 20,21 Our finding highlights the need for health services to ensure parity of esteem 22 between physical and mental health conditions when prioritising groups to be supported by weight loss interventions.…”
Section: Discussionmentioning
confidence: 80%
“…A U.S. study found that access to care for eating disorders decreased among patients with low socioeconomic status during the pandemic (Otto et al, 2021). Previous studies have found that binge eating symptoms were more common in individuals experiencing financial hardship or unemployment during the pandemic (Davies et al, 2022;Mikhail et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers can either submit proposals for participant recontact or access de‐identified data for their own research projects. During the COVID‐19 pandemic, participants were invited to the COVID‐19 Psychiatry and Neurological Genetics (COPING) study, which began at the first UK lockdown to monitor pandemic effects on mental health in which >900 EDGI UK survey participants took part (Davies et al, 2022; Young et al, 2021). As of 2022, EDGI UK is part of the UK Longitudinal Linkage Collaboration (UK LLC), a national collaborative effort for harmonizing health data for longitudinal research.…”
Section: Methodsmentioning
confidence: 99%